Authenticity, belonging, and charter myths of Cantonese. (September 2019) - Wong, Andrew D.
Abstract: Through an analysis of arguments for protecting Cantonese against the encroachment of Putonghua in post-1997 Hong Kong, this article explores tensions in the ideological complex of authenticity and highlights the importance of investigating how spatial and temporal relationships work together to shape understandings of what counts as 'real', 'natural', and 'original'. To endow Cantonese with authority, language advocates in Hong Kong draw on contrasting ideologies of authenticity and construct two distinct charter myths for their mother tongue. Invoking vastly different chronotopes, these ideologies are intimately linked to how Hongkongers view their place in the Chinese nation and the Communist regime. Highlights: Cantonese advocates in Hong Kong draw on contrasting ideologies of authenticity. The two ideologies differ in how they conceptualize time and space. They shape the origin stories of Cantonese. They are linked to how Hongkongers view their place in the Chinese nation. Time and space work together to shape understandings of what counts as authentic.